Tactics: an open-source platform for planning, simulating and validating stereotactic surgery. Issue 1 (1st January 2020) - Adair, David S. P.; Gomes, Keith S.; Kiss, Zelma H. T.; Gobbi, David G.; Starreveld, Yves P.
Abstract: Frame-based stereotaxy is widely used for planning and implanting deep-brain electrodes. In 2013, as part of a clinical study on deep-brain stimulation for treatment-resistant depression, our group identified a need for software to simulate and plan stereotactic procedures. Shortcomings in extant commercial systems encouraged us to develop Tactics. Tactics is purpose-designed for frame-based stereotactic placement of electrodes. The workflow is far simpler than commercial systems. By simulating specific electrode placement, immediate in-context view of each electrode contact, and the cortical entry site are available within seconds. Post implantation, electrode placement is verified by linearly registering post-operative images. Tactics has been particularly helpful for invasive electroencephalography electrodes where as many as 20 electrodes are planned and placed within minutes. Currently, no commercial system has a workflow supporting the efficient placement of this many electrodes. Tactics includes a novel implementation of automated frame localization and a user-extensible mechanism for importing electrode specifications for visualization of individual electrode contacts. The system was systematically validated, through comparison against gold-standard techniques and quantitative analysis of targeting accuracy using a purpose-built imaging phantom mountable by a stereotactic frame. Internal to our research group, Tactics has been used to plan over 300 depth-electrode targets and trajectories in over 50 surgical cases, and to plan dozens of stereotactic biopsies. Source code and pre-built binaries for Tactics are public and open-source, enabling use and contribution by the extended community.